A Review of Orthodontic Archwires - Malik, Nidhi; Dubey, Rachna; Kallury, Amitabh; Chauksye, Ankur; Shrivastav, Trilok; Kapse, Bhagwat Rao (Journal of Orofacial Research, 2015)
Today more than hundred years have passed since Dr Edward angle placed his first archwire into a patient’s mouth and orthodontics began. It was during that period many innovations did occur that have been explained in terms of art. As time passed scientifically based orthodontics evolved and we see from that time much new innovation in material science have sum uped with new treatment approach and modalities. However, when we turn around and see the developments and innovations in the material science, we stand with pride: but the urge to make treatment still more comfortable and less time consuming, have led us to the introduction of a plethora of new orthodontic materials and products that represent significant improvement over their predecessors. This article compiles all archwire from angle era till recent available newer archwire.